Penerapan Metode Perbandingan Eksponensial (MPE) untuk Penentuan Person in Charge (PIC) Teknisi - Rajib Ghaniy; Edi Haryadi (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
PT. MRK Diagnostics is a company engaged in the health sector, especially the provider of medical laboratory equipment in Indonesia. Determination of technicians who are currently running to deal with damage to medical devices is still ineffective because the determination is still checking the availability of technicians manually, so that it will make handling the damage slower. Therefore we need a system that can assist in determining the person in charge technicians to repair the tool. So that in determining the person in charge, this technician will be able to be done precisely and quickly. The criteria used to determine PIC are expertise, discipline, communication and years of service. Each criterion has sub-criteria as well as predetermined weights and values. The decision support system to determine the person-in-charge technicians for medical device repair uses an exponential comparison method that generates a list of priority technicians to perform equipment repair based on calculated and compared values System testing is carried out on information systems experts and users using a questionnaire instrument. Based on expert information systems testing, this system is declared very feasible with a value of 91.7% of the results of system expert testing and 80% based on user testing.